2021
DOI: 10.1177/0956797620979149
|View full text |Cite
|
Sign up to set email alerts
|

Dogs Mentally Represent Jealousy-Inducing Social Interactions

Abstract: Jealousy may have evolved to protect valuable social bonds from interlopers, but some researchers have suggested that it is linked to self-awareness and theory of mind, leading to claims that it is unique to humans. We presented dogs ( N = 18; 11 females; age: M = 4.6 years, SD = 1.9) with situations in which they could observe an out-of-sight social interaction between their owner and a fake dog or between their owner and a fleece cylinder. We found evidence for three signatures of jealous behavior in dogs: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(73 reference statements)
1
3
0
Order By: Relevance
“…The dog behaviours interpreted as jealousy were, for example, squeezing in-between the human–dog interaction (blocking the caregiver from the other dog/social rival), trying to separate the caregiver from the other dog, reacting aggressively by growling, snarling, barking, launching and snapping at the other dog, and trying to regain the caregiver’s attention and affection. Similar to these reports and other behavioural studies investigating jealousy-like behaviours in dogs, we also found that the dogs responded in a rather variable way to a third party their human caregiver was interacting with [ 7 , 8 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The dog behaviours interpreted as jealousy were, for example, squeezing in-between the human–dog interaction (blocking the caregiver from the other dog/social rival), trying to separate the caregiver from the other dog, reacting aggressively by growling, snarling, barking, launching and snapping at the other dog, and trying to regain the caregiver’s attention and affection. Similar to these reports and other behavioural studies investigating jealousy-like behaviours in dogs, we also found that the dogs responded in a rather variable way to a third party their human caregiver was interacting with [ 7 , 8 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Another study using various fake dogs [ 23 ] also found that dogs socially investigated the fake dogs by sniffing the anal region and the muzzle (83% in study 1: with furry fake dog, 78% in study 2: with plastic dog). Moreover, very recently, another study [ 7 ] also showed that 14 out of 15 subject dogs (93%) displayed conspecific-directed behaviours, i.e., sniffed the fake dogs’ (facial and) anal regions when being unleashed after the last test trial (of only observing the interactions), and thus, claimed that they perceived the fake dogs as real dogs [ 7 ]. This is in line with the fact that anogenital sniffing is a common (social) behaviour in dogs to identify the sex or identity of another dog, e.g., when approaching or greeting conspecifics, and hence, might indicate that dogs perceived the fake dog as a real dog or social rival, at least before finally getting closer or physically interacting with it [ 8 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations